Nucleolin, a major conserved multifunctional nucleolar phosphoprotein of proliferating cells - Medina, Francisco Javier; Gonzáez-Camacho, Fernando; Manzano, Ana Isabel; Manrique, Antonio; Herranz, Raúl (Journal of Applied Biomedicine, 2010)
Nucleolin is the major nucleolar protein of animal, plant and yeast proliferating cells. It is enriched in the most soluble nuclear or nucleolar protein extract, containing ribonucleoproteins, from which it has been purified. It has a tripartite structure in which each domain accounts for different functions. Despite its multifunctionality, the best characterized role of nucleolin is in the primary cleavage of pre-rRNA, an early step of ribosome biogenesis. In the nucleolus of proliferating cells, nucleolin is mostly located in the dense fibrillar component, following a vectorial pattern, from the periphery of fibrillar centers outwards. This pattern is lost in quiescent cells in which nucleolin is present in low levels. Nucleolin is the most phosphorylated protein of the soluble nuclear extract. It is phosphorylated by casein kinase II and CDKA, and phosphorylation is closely associated with the role of nucleolin in proliferating cells. During mitosis, nucleolin is transported from the mother to the daughter cell nucleolus in the form of processing particles, together with pre-rRNA precursors and other nucleolar proteins. It forms part of prenucleolar bodies and plays a role in nucleologenesis. Recent studies on the nucleolin function, carried out on samples with inactivated nucleolin genes (siRNA downregulated or mutants) have evidenced that nucleolin is absolutely essential for cell proliferation, for the organization of the nucleolus and for transcription and processing of pre-rRNA. In plants, nucleolin controls the auxin responsiveness, thus being involved in the regulation of plant development.
Keywords: Ribosomes; Animals; Nuclear Proteins; Statistics as Topic; proliferace buněk; klinické laboratorní techniky; fosfoproteiny; Clinical Laboratory Techniques; statistika jako téma; jaderné proteiny; Cell Cycle; prekurzory RNA; proteiny vázající RNA; Indoleacetic Acids; Phosphoproteins; Organelle Biogenesis; Yeasts; ribonukleoproteiny malé jadérkové; rostliny; buněčný cyklus; Ribonucleoproteins, Small Nucleolar; fosforylace; kvasinky; kyseliny indoloctové; Cell Proliferation; RNA Precursors; RNA-Binding Proteins; Plants; ribozomy; zvířata; biogeneze organel; Phosphorylation